IMPROVEMENT OF MATHEMATICS LEARNING OUTCOMES OF GRADE III ELEMENTARY SCHOOL STUDENTS APPLYING THE MAKE A MATCH LEARNING MODEL - Rahmi Hidayati; Yulia Futri; Firda Halawati (Jurnal Math-UMB.EDU, 2025)
The aim of this study was determining the effectiveness of the application of the make-a-match learning model in learning mathematics. The study is a quantitative experimental study with the population being students in one of the elementary schools in Balangan Regency and the sample being grade III students in the elementary school. To measure the activity of learning activities, the data analysis used is descriptive statistics to find out how effective the application of the make-a-match learning model is for grade III elementary school, a on-paired sample test was carried out. The results of the study showed that in learning mathematics on fractions in grade III by applying the make-a-match learning model, there was an increase in students' mathematics learning activities as reviewed from student learning outcomes of 71.2%, classically completeness reached up to 90% and learning implementation was 77.1%. The results of the effectiveness of the application-of-the make-a-match learning model itself were declared effective, this was seen from the sig value of 0.000 less than 0.005 which stated that the average completeness of learning outcomes reached and exceeded the KKM. Keywords: mathematics learning, make-a-match, learning outcomes